Dismounted Blast Injuries in Patients Treated at a Role 3 Military Hospital in Afghanistan: Patterns of Injury and Mortality. Issue 9 (1st September 2016) - Oh, John S.; Tubb, Creighton C.; Poepping, Thomas P.; Ryan, Paul; Clasper, Jonathan C.; Katschke, Adrian R.; Tuman, Caroline; Murray, Michael J.
ABSTRACT: Background: The purposes of this study are to define the pattern of injuries sustained by dismounted troops exposed to improvised explosive devices blasts treated at a Role 3 combat support hospital and to assess injury patterns and mortality associated with the mechanism. Our hypothesis was that mortality is associated with pelvic fracture, massive transfusion, high Injury Severity Score (ISS), multiple limb amputations, and transfer from a Role 2 facility. Study Design: Retrospective study of 457 patients. Analysis performed on trauma registry data and systematic review of radiographs. Results: 99.9% were men with a median age of 23 years and median ISS 10. 141 patients (30.9%) required massive blood transfusion. Limb amputations were frequently observed injuries, 109 of 172 amputees (63.4%) had a double amputation. 34 subjects (7.4%) had pelvic fractures; majority of pelvic fractures (88%) were unstable (Tile B or C). Risk factors associated with the overall mortality rate of 1.8% were an ISS greater than 15 (odds ratio: 11.5; 95% confidence interval: 1.38, 533; p = 0.009), need for massive transfusion ( p < 0.0001), and the presence of a pelvic fracture (odds ratio: 7.63; 95% confidence interval: 1.13, 41.3; p = 0.018). Conclusions: Dismounted improvised explosive devices blast injuries result in devastating multiple limb amputations and unstable pelvic fractures, which are associated with mortality after initial trauma resuscitation at a Role 3 hospital.